Geometrical effect, optimal design and controlled fabrication of bio-inspired micro/nanotextures for superhydrophobic surfaces. (4th September 2017) - Ma, F M; Li, W; Liu, A H; Yu, Z L; Ruan, M; Feng, W; Chen, H X; Chen, Y
Abstract: Superhydrophobic surfaces with high water contact angles and low contact angle hysteresis or sliding angles have received tremendous attention for both academic research and industrial applications in recent years. In general, such surfaces possess rough microtextures, particularly, show micro/nano hierarchical structures like lotus leaves. Now it has been recognized that to achieve the artificial superhydrophobic surfaces, the simple and effective strategy is to mimic such hierarchical structures. However, fabrications of such structures for these artificial surfaces involve generally expensive and complex processes. On the other hand, the relationships between structural parameters of various surface topography and wetting properties have not been fully understood yet. In order to provide guidance for the simple fabrication and particularly, to promote practical applications of superhydrophobic surfaces, the geometrical designs of optimal microtextures or patterns have been proposed. In this work, the recent developments on geometrical effect, optimal design and controlled fabrication of various superhydrophobic structures, such as unitary, anisotropic, dual-scale hierarchical, and some other surface geometries, are reviewed. The effects of surface topography and structural parameters on wetting states (composite and noncomposite) and wetting properties (contact angle, contact angle hysteresis and sliding angle) as well as adhesive forces are discussed in detail. Finally, the research prospects in this field are briefly addressed.